Drought has negative consequences on aphid fitness and plant vigor: Insights from a meta‐analysis. Issue 17 (28th July 2021) - Leybourne, Daniel J.; Preedy, Katharine F.; Valentine, Tracy A.; Bos, Jorunn I. B.; Karley, Alison J.
Abstract: Aphids are abundant in natural and managed vegetation, supporting a diverse community of organisms and causing damage to agricultural crops. Due to a changing climate, periods of drought are anticipated to increase, and the potential consequences of this for aphid–plant interactions are unclear. Using a meta‐analysis and synthesis approach, we aimed to advance understanding of how increased drought incidence will affect this ecologically and economically important insect group and to characterize any potential underlying mechanisms. We used qualitative and quantitative synthesis techniques to determine whether drought stress has a negative, positive, or null effect on aphid fitness and examined these effects in relation to (a) aphid biology, (b) geographical region, and (c) host plant biology. Across all studies, aphid fitness is typically reduced under drought. Subgroup analysis detected no difference in relation to aphid biology, geographical region, or the aphid–plant combination, indicating the negative effect of drought on aphids is potentially universal. Furthermore, drought stress had a negative impact on plant vigor and increased plant concentrations of defensive chemicals, suggesting the observed response of aphids is associated with reduced plant vigor and increased chemical defense in drought‐stressed plants. We propose a conceptual model to predict drought effects on aphid fitness in relation to plant vigor and defense to stimulate further research. Abstract : Using meta‐analysis, we provide the first comprehensive analysis of drought stress on aphid fitness, showing negative effects across different host plant families, aphid tribes, and geographic regions. These negative effects were observed for different aphid fitness parameters and host specialisms and likely result from drought‐induced reduction in plant vigor and increased tissue concentrations of plant‐defensive compounds.